Green Tea Polyphenol Epigallocatechin-3-Gallate Promotes Reendothelialization in Carotid Artery of Diabetic Rabbits by Reactivating Akt/eNOS Pathway - Huang, He; Jin, Chong-ying; Bi, Xu-kun; Zhao, Yan-bo; Xu, Sheng-jie; Wang, Mei-hui; Yu, Lu; Sun, Ya-xun; Hu, Dan (Frontiers in Pharmacology, 2018)
Background: Epigallocatechin gallate (EGCG) is the most abundant catechin in green tea and has proven benefits on endothelial cells in diabetes. However, it remains unclear whether EGCG could improve function of late endothelial progenitor cells (L-EPCs) in diabetes. Methods: Thirty-six rabbits were randomized into six groups. Thirty diabetic rabbits were induced by a single dose of alloxan (100 mg/kg injection intraperitoneally). All of them were given intragastrically EGCG (50 mg/kg/day) or saline for 7 days after carotid injury. In autotransfusion experiment, L-EPCs were cultured with pre-treated EGCG (40 μM for 72 h) and then were injected into the site of injured vascular. Proliferation and migration of EGCG pre-treated L-EPCs in high glucose condition were assessed by EDU incorporation assay and modified Boyden chamber assay, respectively. The mRNA and protein expression of Akt-eNOS pathway were detected by real-time PCR and western blot. Results: Reendothelialization rate in injured carotid artery of diabetic rabbits was augmented in the EGCG group (50 mg/kg/d for 7 days) compared with the non-EGCG group (74.2 ± 4.6% vs. 25.6 ± 5.9%, P < 0.001). EGCG pre-treated L-EPCs autologous transfusion also accelerated the diabetic rabbits’ carotid reendothelialization compared with the diabetic sham-operated group (65.6 ± 8.5% vs. 32.9 ± 5.0%, P = 0.011). In vitro studies showed, 40 μM EGCG treatment for 72 h recovered L-EPCs’ proliferation and migration, as well as restored the phosphorylation level of Akt and eNOS blocked by high glucose condition. Conclusion: EGCG accelerated reendothelialization in diabetic rabbits after carotid injury in part by reactivating the Akt/eNOS pathway, which might contribute to recovering proliferation and migration of L-EPCs impaired by high glucose.